Content Analysis From a Gender Perspective of Comments Received by Spanish Science YouTubers - Cambronero Saiz, Belén; Cristófol Rodríguez, Carmen; Segarra-Saavedra, Jesús (Media and Communication, 2023)
One of the main features of videos that popularise science on YouTube is the ability to interact with the videos and the YouTubers who generate them. However, some types of interaction are often not gender neutral. In order to identify whether there are gender differences in the type of comments posted on YouTube channels that popularise science, a content analysis of nine such channels hosted by Spanish macro influencers was conducted. A total of 221 videos and 18,873 comments were analysed to identify and classify comments of a personal nature relating to physical appearance, tone of voice, or intellectual capacity, among other aspects. The results show that 7.5% (1,424) of the total number of analysed comments were comments of a personal nature addressed to the channel’s host. Of the videos hosted by women, 95.3% contained at least one positive comment related to their physical appearance, compared to 27% in the case of men. Gender differences were mainly found in negative comments regarding the presenter’s intellectual ability or personality, with women most likely to receive them. These results show that women who face media exposure are more vulnerable to negative sexist comments, which may deter them from professionalisation in this area.
Keywords: gender; science communication; sciencetubers; sentiment analysis; YouTube; Scopus; JCR